Key Global Treaties and Socio-Cultural Rights: Analyzing Historical Implications, Implementation Challenges, And Community Voices - Thusikkhanth, S. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
This study focuses on the impact of law and humanity in the modern world, protecting social and cultural rights and providing them to future generations. The primary objective of this study is to analyze how the background of world historical events such as the world wars has influenced the creation of global treaties. The aim of this study is to analyze the influence of the International Covenant on Economic, Social and Cultural Rights (ICESCR) and the International Covenant on Civil and Political Rights (ICCPR), which are considered important treaties in world history, through a qualitative method to examine how they have affected social structures and how each society has dealt with them. While global treaties have brought positive change, it also examines the challenges in implementing them. For this, interviews and discussions with members of minorities, oppressed communities, indigenous peoples, and poor populations are the basis for the data. Collaboration with non-governmental organizations enhances the diversity of the data. The lack of strong international accountability, various domestic legal systems, limited resources and the possibility of some powerful countries withdrawing from global treaties limit the scope of the treaties, and whether rights are shared equally for all people, and whether everyone has access to education, health, food and land due to administrative obstacles and political instability, is the theme examined. Language barriers and cultural barriers that limit access to research data emphasize the need to consider people’s contexts. By examining the impact of global treaties on socio-cultural rights, this study seeks to highlight the successes achieved and the obstacles encountered, and to give voice to the people affected by them. This study expects that global treaties must be further strengthened and that humanity will flourish through the dedication of human rights activists and law reformers to ensure that all people enjoy human rights equally.
Keywords: Socio-cultural rights; International covenant on civil and political rights (ICCPR); World wars; Administrative obstacles; Human rights activists